2015
DOI: 10.1001/jamadermatol.2015.0174
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Adhesive Strips and Dermal Sutures vs Dermal Sutures Only on Wound Closure

Abstract: IMPORTANCE Although applying adhesive strips to a wound closure has been shown to have outcomes equivalent to those with cuticular suturing, it is unknown whether adhesive strips provide additional benefit compared with dermal suturing alone. OBJECTIVE To determine whether the addition of adhesive strips to a wound closed with buried interrupted subcuticular sutures improves outcomes following wound closure. DESIGN, SETTING, AND PARTICIPANTS A prospective, randomized split-wound intervention was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 15 publications
0
25
0
Order By: Relevance
“…An updated Cochrane review [27] was carried out to determine the effects of various tissue adhesives compared with conventional skin closure techniques for the closure of surgical wounds included 33 studies with a total of 2793 participants and demonstrated that there was lowquality evidence that sutures were significantly better than tissue adhesives for reducing the risk of wound breakdown (dehiscence; RR 3.35; 95% CI 1.53 to 7.33; 10 trials, 736 participants that contributed data to the meta-analysis). The number needed to treat for an additional harmful outcome was calculated as 43.…”
Section: Resultsmentioning
confidence: 99%
“…An updated Cochrane review [27] was carried out to determine the effects of various tissue adhesives compared with conventional skin closure techniques for the closure of surgical wounds included 33 studies with a total of 2793 participants and demonstrated that there was lowquality evidence that sutures were significantly better than tissue adhesives for reducing the risk of wound breakdown (dehiscence; RR 3.35; 95% CI 1.53 to 7.33; 10 trials, 736 participants that contributed data to the meta-analysis). The number needed to treat for an additional harmful outcome was calculated as 43.…”
Section: Resultsmentioning
confidence: 99%
“…Split-scar models have been used in the past to assess cuticular suturing techniques. [2][3][4] Ethical approval was obtained through the University of California, Davis Institutional Review Board before study commencement, and all patients provided verbal and written informed consent to enrollment. The trial protocol can be found in the Supplement.…”
Section: Methodsmentioning
confidence: 99%
“…Ethical approval was obtained through the University of California, Davis Institutional Review Board before study commencement, and all patients provided verbal and written consent to enrollment. To minimize the number of uncontrolled variables, a split scar model was used, in congruence with past studies that have looked at cuticular suturing techniques [11][12][13].…”
Section: Methodsmentioning
confidence: 99%
“…The total score ranges from 6 to 60 with a lower score representing more normal appearing skin on the scale. The POSAS has been validated when 2 independent observers are used [18] and has been used in numerous surgical studies [12,13,17,[19][20][21][22][23][24][25]. The scar outcome was evaluated in person by the patient and 2 blinded observers who were not present during the intervention.…”
Section: Assessmentsmentioning
confidence: 99%